1996
DOI: 10.3109/13816819609057864
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in 55 patients with Down's syndrome

Abstract: Fifty-five patients with Down's syndrome were examined to evaluate the characteristics and frequency of ocular findings. Of these patients, 29 (52.7%) were hypermetropes, 7 (12.7%) were emmetropes, and 7 (12.7%) were myopes; astigmatism of more than 3.00 diopters was present in 7(12.7%) patients. Strabismus was observed in 12 (21.8%) patients. All but one of these 12 patients also had esotropia. Congenital nasolacrimal duct obstruction was present in 12 subjects (21.8%). Blepharitis was found in 19 (34.5%) cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
4
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 11 publications
9
64
4
3
Order By: Relevance
“…Although it is difficult to compare our results with previous studies because of the variegated definitions of refractive error, the prevalences of myopia and hyperopia in our study appear to be similar to those reported in earlier studies. 10 However, the prevalence of astigmatism was different from those studies, with an almost twofold increase noted in our study. 3 In addition, the prevalence of astigmatism increased with age in earlier studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Although it is difficult to compare our results with previous studies because of the variegated definitions of refractive error, the prevalences of myopia and hyperopia in our study appear to be similar to those reported in earlier studies. 10 However, the prevalence of astigmatism was different from those studies, with an almost twofold increase noted in our study. 3 In addition, the prevalence of astigmatism increased with age in earlier studies.…”
Section: Discussioncontrasting
confidence: 55%
“…The overall incidence of ocular abnormalities in Korean children with DS (91%) was markedly higher than previously reported (Table 5). [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] This might be due to the preparation of a special examination sheet for DS documenting every reported ocular finding, slit-lamp biomicroscopy (before and after fluorescein instillation), cycloplegic refraction, and indirect ophthalmoscopic examination for every patient. The ocular findings in Korean children with DS are characterized as an unreported, high incidence of epiblepharon, the highest rate of exotropia and no cases of Brushfield spots.…”
Section: Discussionmentioning
confidence: 99%
“…1 Numerous ophthalmic features have been reported, including abnormalities of the eyelid, cornea, iris, lens, retina, and optic disc, as well as ametropia, amblyopia, strabismus, and nystagmus. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The incidence of each ocular abnormality varies in different studies. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most reported studies of ocular findings in DS have been performed in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discuss obesity as a risk factor for sleep apnea. 34 It is recognized that access to a pediatric sleep laboratory or specialist may be limited for some populations and geographic areas.…”
Section: The Symptomatic Childmentioning
confidence: 99%